IMPLEMENTATION OF COLD CHAIN SYSTEM IN PEELED DEVEINED TAIL-ON VANNAMEI SHRIMP (Litopenaeus vannamei) PRODUCTS - Panjaitan, Fenny Crista Anastasia; Samanta, Pinky Natalia; Utari, Siluh Putu Sri Dia; Br. Sitepu, Gressty Sari (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
Vannamei (Litopenaeus vannamei) Peeled Deveined Tail-On (PDTO) shrimp is frozen shrimp product consumers highly preferred. However, shrimp products are easily perishable that require a proper cold chain system to preserve their quality, shelf life, and nutritional value. This study investigated the cold chain implementation of PDTO shrimp processing in the fishery industry. The temperature of shrimp products, water, and rooms was monitored during processing. Results showed that the shrimp temperature measured in each process was below 5°C. However, abusive temperatures were detected in water used in the peeling and deveining step and soaking process, while water and shrimp temperatures altered each other. Moreover, room temperatures were recorded under 20°C, conforming to Ministry of Marine and Fisheries regulations. Air Blast Freezer and cold storage temperatures revealed that ABF and CS could not meet the company’s temperature standards. These findings may help shrimp companies monitor steps indicating to have temperature abuse attentively.